Pliocene - present tectonics and strain rate in Ninh Thuan region and surrounding continental shelf - Liem, Ngo Van; Trinh, Phan Trong; Phong, Tran Van; Lien, Vy Thi Hong; Huong, Nguyen Van; Xuyen, Nguyen Quang; Thanh, Bui Nhi; Hao, Duong Van; Pham, Binh Thai; Dung, Nguyen Van; Dang, Vu Khac; An, Vu Hoa (Vietnam Journal of Earth Sciences, 2020)
In this paper, we present detail data of Pliocene - present tectonics and strain rate from GPS measurement and seismic interpretation. Using international reference frame ITRF08, we revealed absolute tectonic velocities of GPS sites with the slip rate to the east between 22 to 25 mm/year, to the south between 4 to 8 mm/year. The present strain rate was determined from present tectonic velocities that were consistent with the recent strain rates determined from seismic profiles, thickness of Pliocene - Quaternary sediments. Present day strain rate varying from 10 to 30 nano per year indicated that the region has been deformed weakly, in a stable tectonic regime.